Landscapes of devils : tensions of place and memory in the Argentinean Chaco - Gordillo, Gastón (e-Duke books scholarly collection., 2004)
Landscapes of Devils is a rich, historically grounded ethnography of the western Toba, an indigenous people in Northern Argentina's Gran Chaco Region.